Study on the Bending Capacity of Cold-formed Stainless Steel Hollow Sections. (November 2016) - Zheng, Baofeng; Shu, Ganping; Xin, Lianchun; Yang, Ran; Jiang, Qinglin
Abstract: Experimental and numerical studies on the bending capacity of cold-formed stainless steel rectangular and circular hollow sections are reported. Eight four-point bending tests were carried out. Material properties, geometric imperfections, bending capacities, moment-curvature curves were obtained in the tests. Finite element models were developed, and were verified using the test data. Material nonlinearity and geometric imperfections were considered in the modeling. Parameter studies were conducted to expand test data with different material properties and section slenderness. Based on the test results and the finite element analysis results, direct strength formulas were proposed for rectangular and circular hollow sections, respectively. Test data were collected from literatures as references, and compared with predictions of the Eurocode, the American code, the Australian/New Zealand code, the Chinese code, and the continuous strength method (CSM). Comparisons show that the Eurocode, the American code, the Australian/New Zealand code, and the Chinese code are generally conservative. The Chinese code provides most conservative predictions, due to the neglect of strain hardening effect and section plasticity, especially for stocky cross sections. The performance of CSM method is better than the design codes. The proposed formulas show better accuracy in predicting bending capacities of cold-formed stainless steel hollow sections.